Pengaruh Pengaturan Posisi Semi Fowler terhadap Lama Pemulihan Kesadaran Pasien Post Operasi dengan General Anestesi - Siti Hajar; Suyanto; Retno Setyawati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Postoperative consciousness recovery in patients who have received general anesthesia sometimes experiences delays, which can lead to postponing the transfer of patients to the recovery room. One approach that nurses can use to accelerate consciousness recovery after general anesthesia is by adjusting the patient’s sleeping position. This study aims to determine the effect of the semi-Fowler position on the length of consciousness recovery in postoperative patients with general anesthesia. The research method is quasi-experimental with a posttest-only control group design. The sample consisted of 42 postoperative patients with general anesthesia at RSUD dr. H. Soewondo Kendal, divided into two groups: the intervention group and the control group, selected using consecutive sampling technique. Data analysis was performed using the independent sample t-test. The results showed that most patients were aged 36-45 years, male, with the most commonly used anesthetic being Laryngeal Mask Airway (LMA) and the duration of surgery was less than 1 hour. The average consciousness recovery time for patients in the semi-Fowler position was 11.19 minutes, categorized as quick recovery. Meanwhile, the average consciousness recovery time for patients in the supine position was 15.0 minutes, also categorized as quick recovery. The analysis showed a significant effect of the semi-Fowler position on the consciousness recovery time (p-value = 0.048). In conclusion, the semi-Fowler position can accelerate consciousness recovery time by 3.81 minutes compared to the supine position in postoperative patients with general anesthesia.